Determination of the UV absorber 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) and its oxidative metabolites in human urine by dispersive liquid-liquid microextraction and GC–MS/MS - Denghel, Heike; Göen, Thomas (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2020)
2-(2H-Benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) is an ultraviolet light (UV) absorber which prolongs the stability of plastics and other organic compounds towards UV radiation. Therefore, it is frequently used as a preserving additive and may result in an exposure of consumers. Thus, an analytical method using dispersive liquid-liquid microextraction and subsequent gas chromatography tandem mass spectrometry analysis with advanced electron ionization was developed for a human biomonitoring of UV 328 exposure, which enabled the determination of UV 328 and six of its metabolites in human urine. Sample preparation and derivatization were optimized. Baseline separation of the analytes was assured by the application of a suitable temperature program. The validation resulted in limits of detection of 0.1 µg/L for all analytes, variation coefficients from 1 to 12% for precision in series and from 5 to 12% for interday precision. Furthermore, relative recovery rates between 80 and 120% were determined. Moreover, the procedure was successfully applied to urine samples of a volunteer exposed to UV 328. The method showed excellent sensitivity, repeatability and robustness for all parameters and may be applicable for studies to elucidate the metabolism and kinetics of the investigated UV absorber and for monitoring of individuals with specific exposure to UV 328.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Dispersive liquid-liquid microextraction; Human biomonitoring; Metabolites; Urine analysis; UV 328; UV absorber